DESIGN AND CONSTRUCTION OF A WEB-BASED SAGO WASTE MANAGEMENT AND MARKETING INFORMATION SYSTEM TO SUPPORT A LOCAL CIRCULAR FOOD ECONOMY: RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DAN PEMASARAN LIMBAH SAGU BERBASIS WEB GUNA MENDUKUNG EKONOMI SIRKULAR PANGAN LOKAL - Deril Alfiance Kaligis; Nurul Qisti (ROCE : Jurnal Pertanian Terapan, 2026)
Sago processing waste, particularly sago pulp, often poses environmental problems due to inadequate disposal management, despite its significant economic potential within a circular economy framework. The main obstacles to its utilization are the availability of decentralized production data and limited market access for local food businesses. This research aims to design and build a web-based system to manage and market sago waste, facilitating transactions between waste producers and industrial users. The system development method used is the Waterfall method, which includes requirements analysis, system design using UML, coding in PHP and MySQL, and testing. The results show that this information system successfully integrates real-time waste data collection and provides a transparent marketplace feature. Black Box testing confirmed that all system functions operate according to user requirements. The implementation of this platform can support a circular economy by converting waste into an economically valuable resource while reducing negative environmental impacts on the local food ecosystem.